INFLUENCE OF PARTICIPATIVE LEADERSHIP STYLE ON EMPLOYEE JOB SATISFACTION IN COMMERCIAL BANKS IN KENYA - Mwaisaka, Davidson Mghanga; K'Aol, Prof. George; Ouma, Dr. Caren (European Journal of Business and Strategic Management, 2019)
Purpose: The study investigated the influence of participative leadership style on job satisfaction of employees within commercial banks in Kenya. Methodology: It was guided by positivism philosophy and descriptive correlation research design. The targeted population comprised of 15,030 employees, who report to middle level managers in all the 43 commercial banks licensed to operate in Kenya. Using stratified random sampling technique, a sample size of 389 was determined. Primary data was collected through a self-administered structured questionnaire, and was analyzed using descriptive and inferential statistics. Out of 389 questionnaires administered, 370 were successfully completed and returned representing a response rate of 95%. The descriptive statistics used included mean, frequency distribution and standard deviations. Inferential statistics on the other hand included correlation, Chi-Square tests, one-way analysis of variance (ANOVA) and multiple linear regression analysis. The statistical tool used for data analysis was Statistical Package for Social Sciences (SPSS) Version 20. The results were presented in tables and figures. Findings: The correlation analysis for the study showed that participative leadership style significantly influence employee job satisfaction, r(370) = .820, p < .05. Multiple linear regression analysis revealed that participative leadership style positively and significantly predicted employee job satisfaction, R2 = .500, F(1, 364) = 181.811, p < .05; Î² = .673, p < .05. As a result, the study rejected the null hypothesis; participative leadership style has no significant influence on employee job satisfaction. Unique Contribution to Theory, Practice and Policy: The study recommends that there should be the inclusion of all employees in the process of determining the influence of path-goal leadership style on employee job satisfaction.